An assessment of technological competencies on professional service firms business performance - Ainin, S.; Kamarulzaman, Y.; Farinda, A.G. (2010)
This study was initiated with a three prong objective. One, to identify the relationship between Technological Competencies factors (Technical Capability, Firm Innovativeness and E-Business Practices and professional service firms’ business performance. Two, to investigate the predictors of professional service firms business performance and finally to evaluate the predictors of business performance according to the type of professional service firms. A survey questionnaire was deployed to collect empirical data. The questionnaire was distributed to the owners of the professional small medium size enterprises services in the Accounting, Legal, Engineering and Architecture sectors. Analysis showed that all three Technology Competency factors have moderate effect on business performance. In addition, the regression models indicate that technical capability is the most highly influential that could determine business performance, followed by e-business practices and firm innovativeness. Subsequently, the main predictor of business performance for all types of firms is Technical capability